"I Did Not Want to Give Birth to a Child Who has HIV": Experiences Using PrEP During Pregnancy Among HIV-Uninfected Kenyan Women in HIV-Serodiscordant Couples. (1st November 2017) - Pintye, Jillian; Beima-Sofie, Kristin M.; Kimemia, Grace; Ngure, Kenneth; Trinidad, Susan Brown; Heffron, Renee A.; Baeten, Jared M.; Odoyo, Josephine; Mugo, Nelly; Bukusi, Elizabeth A.; Kelley, Maureen C.; John-Stewart, Grace C.
Abstract : Objectives: The perceptions, motivations, and beliefs of HIV-uninfected women about pre-exposure prophylaxis (PrEP) use during pregnancy can influence its uptake and adherence. This study elicited the views of HIV-uninfected women with personal experience taking PrEP during pregnancy. Design: Qualitative interviews were conducted with HIV-uninfected women who had personal experience taking PrEP while pregnant. Methods: Semistructured interviews were conducted with 21 HIV-uninfected Kenyan women in HIV-serodiscordant couples enrolled in an open-label PrEP demonstration project who became pregnant while using PrEP and continued PrEP through their pregnancy. Interviews were audio-recorded and transcribed into English. A qualitative descriptive analysis was performed, using a constant comparison approach to identify key themes related to PrEP use in pregnancy. Results: Desire to remain HIV uninfected and have an HIV-free infant were strong motivators influencing continued use of PrEP during pregnancy. Supporting HIV-infected partners and childbearing within an HIV-serodiscordant relationship were also motivators. Women had challenges distinguishing normal pregnancy symptoms from PrEP side effects and were concerned that observed side effects could be signs of danger for the infant related to PrEP exposure. Health care providers were important conduits of knowledge about PrEP, and continuity of PrEP providers throughout pregnancy facilitated adherence. Conclusions: HIV-uninfected women in HIV-serodiscordant couples were motivated to use PrEP during pregnancy to remain HIV uninfected and to have an HIV-free child but had concerns about side effects. Health care providers will be important for PrEP messaging and adherence support in this unique population. Abstract : Supplemental Digital Content is Available in the Text.